Temporal summation--the key to motor evoked potential spinal cord monitoring in humans. Issue 1 (January 1993) - Taylor, B A; Fennelly, M E; Taylor, A; Farrell, J
Abstract : Spinal motor evoked potentials (SMEP) were recorded from tibialis anterior muscle after epidural stimulation of the spinal cord at the low cervical or high thoracic level during scoliosis surgery. By using a double stimulus pulse to produce temporal summation within the spinal cord a maximal CMAP response was readily achieved despite good surgical anaesthesia.